(untitled) (Northern International Medical College Journal, 2015)
Total abdominal Hysterectomy are gradually rising in our country. This study has been designed to find out the common indications of abdominal hysterectomy in a tertiary care hospital,. to know the clinical characters of the patients and. o elucidate postoperative complication of abdominal hysterectomy. Methodology : Cross- sectional observational study was done during 1st October 2007 to 30th September 2008. Holy Family Red Crescent Medical College Hospital (HFRCMCH). Total 100 patients were selected following enclusion & exclusion criteria hyperposive sampling. Data were recorded before and after operation and analyzed by SPSS version 15. Result : In the present study patients with leiomyoma of uterus was found to be the major indication of hysterectomy followed by dys functional uterine bleeding (DUB) 18.0%, Pelvic inflammatory disease (PID) 14.0%, chronic cervicitis 10.0%, adenomyosis 10.0%, pelvic endometriosis 6.0%, cervical polyp 2.0%, ovarian cysts 1.0% and chriocarcinoma 1.0%. Mean duration of operation (hour) and hospital stay was 1.15 hours and 7.48 days respectively. Most common complication of present series was fever 20.0% followed by 13.0% had wound infection, 6.0% UTI and 2.0% wound dehiscence. Conclusion : Hysterectomy is now the most widely performed major operation in gynaecology. Indication and post operative complications of hysterectomy varies from region to region. Northern International Medical College Journal Vol.6(2) 2015: 76-77